Peran Pendidikan Islam dalam Pengembangan Karakter Keluarga: Strategi Pembinaan Iman, Ibadah, dan Akhlak di Era Globalisasi dan Digitalisasi - M Rizqil Hasan Muqorrobin; Ainur Rofiq Sofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the role of Islamic education in character development within the family, focusing on strategies for fostering faith, worship, and ethics in the face of the challenges of globalization and digitalization. The family, as the primary educational institution, plays a crucial role in shaping the character of children, encompassing spiritual, moral, and social development. In the modern era, external influences through social media and globalization present significant challenges to family education, particularly in maintaining faith, practicing worship, and developing noble ethics. This research employs a qualitative approach, using literature review and in-depth interviews with parents and Islamic educators. The findings indicate that the strategy for fostering faith is carried out through the teaching of religious values, such as discipline in worship, and strengthening the relationship with Allah SWT. Worship development is emphasized through the practice of congregational prayer and voluntary worship, while the formation of ethics is achieved through role modeling, positive communication, and the habitual practice of good behavior in daily life. However, families face considerable challenges in implementing these educational strategies, including the influence of foreign cultures, the misuse of technology, and the busyness of parents. Nonetheless, with the wise use of technology and consistent family-based education, the goals of character education based on faith, worship, and ethics can be achieved. This study provides recommendations for parents and educators to continue strengthening the role of the family in educating children by emphasizing the importance of Islamic values in everyday life and utilizing technology to support positive educational processes